Evaluation of Parking Space Needs at Medika Dramaga Hospital - Riki, Muhamad; Rulhendri, Rulhendri; Alimuddin, Alimuddin (ASTONJADRO, 2026)
Medika Dramaga Hospital is located in Margajaya Village, West Bogor District, Bogor City. This hospital is owned by a private party, has obtained an operational permit for health services since 2010. With the increasing population density of West Bogor, of course visits to the Hospital will also increase, therefore it is necessary to have supporting facilities such as adequate parking areas so that visitors feel safe and comfortable when parking their vehicles. In this study using the SRP characteristic method (Volume, Accumulation, Duration, Over Turn Over, Index), in this study is the Evaluation of Parking Space Needs. Data collection was carried out using a survey method with a time of 10 hours and running for seven days with the aspects taken being data on vehicle entry and exit times to determine parking characteristics. The results of this study indicate that the need for parking space cannot accommodate motorcycles, an area of ​​285m2 has a parking capacity of 70 SRP. In this analysis study, the results of the largest accumulated static capacity were 75 vehicles with an average parking duration of 09:23 hours on the peak day, namely Thursday, February 6, 2025. During the seven days of the survey, it was found that the maximum parking volume was 171 vehicles with a maximum vehicle parking accumulation of 120 vehicles which occurred on Monday, February 3, 2025. The highest motorcycle parking turnover at Medika Dramaga Hospital reached 244.29%, indicating that motorcycle parking performance is quite high. The capacity of motorcycle parking space at Medika Dramaga Hospital cannot meet existing parking needs. This is indicated by looking at the parking index exceeding 100%.